New Drought-Tolerant Crops for Resilient Dryland Livelihoods - ICARDA, Communication Team (International Center for Agricultural Research in the Dry Areas, 2023)
An international collaboration of world-leading scientists led by ICARDA Morocco has delivered six ground-breaking new durum wheat and barley varieties tolerant to increasingly severe droughts ravaging the region.